Association study of glucocorticoid receptor genetic polymorphisms with efficacy of glucocorticoids in systemic lupus erythematosus: A prospective cohort study. (23rd October 2013) - Zou, Yan-Feng; Xu, Jian-Hua; Wang, Fen; Liu, Shuang; Tao, Jin-Hui; Cai, Jing; Lian, Li; Xiao, Hui; Chen, Pei-Ling; Tian, Guo; Wu, Min; Wang, De-Guang; et al.
Abstract: The response to glucocorticoids (GCs) for patients with systemic lupus erythematosus (SLE) is characterized by wide interindividual variability, with a significant number of patients who have no response. We analyzed whether genetic polymorphisms within glucocorticoid receptor (GR) gene are related to variability in the efficacy of GCs in Chinese population with SLE. A cohort of 220 patients with SLE was studied. These patients were treated with GCs (prednisone) for 12 weeks. The efficacy of GCs was measured with the scores on SLE disease activity index (SLEDAI). Patients were classified into two groups (sensitive and insensitive) according to their response to GCs. Polymorphisms of GR gene were genotyped by using multiplex SNaPshot method. A total of 212 patients (96.4%) were included in the final data analyses. Of these patients, 110 patients were considered sensitive to GCs, and 102 patients were considered insensitive to GCs. Eighteen tag single nucleotide polymorphisms (SNPs) of GR gene were selected. Significant associations were seen for rs4912905 (dominant model: crude OR = 0.410, 95%CI = 0.233–0.722, p  = 0.002; adjusted OR = 0.419, 95%CI = 0.233–0.754, p  = 0.004), rs17100234 (dominant model: crude OR = 0.521, 95%CI = 0.282–0.963, p  = 0.038; adjusted OR = 0.520, 95%CI = 0.279–0.970, p  = 0.040) and rs7701443 (recessive model: crude OR = 2.736, 95%CI = 1.183–6.331, p  = 0.019; adjusted OR = 2.639, 95%CI = 1.116–6.239, p  = 0.027) in GR gene, but not for other polymorphisms ( p  > 0.05). The results of the present study suggest that GR genetic polymorphisms may play a major role in the efficacy of GCs in Chinese population with SLE.